Reward‐based or meaningful gaming? A field study on game mechanics and serious games for sustainability. Issue 6 (11th March 2021) - Whittaker, Lucas; Russell‐Bennett, Rebekah; Mulcahy, Rory
Abstract: Despite investigating digital gaming for commercial purposes, less scholarly attention exists on digital gaming for societal purposes such as sustainability ("serious games"). The current study investigates whether a serious game can enhance sustainability marketing outcomes, including knowledge, value‐in‐behavior, and behavioral intentions longitudinally (pre‐gameplay to post‐gameplay). Further, the study seeks to understand the influence of reward‐based and meaningful game mechanics on these sustainability marketing outcomes. We recruited 387 participants for a week‐long field study using a serious game which encourages household energy conservation. The findings show that the serious game significantly increased sustainability knowledge, value‐in‐behavior, and sustainable behavioral intention after one week. Reward‐based game mechanics (badges and trophies) significantly influenced sustainability knowledge and indirectly influenced value‐in‐behavior via sustainability knowledge, whereas reward‐based (points) and meaningful (educational messages) game mechanics had little impact. The results empirically support the conceptual model theorization—underpinned by a "do–learn–feel" behavioral learning approach—which possessed superior fit to a "do–feel–learn" rival model. This study provides novel insights regarding eliciting value‐in‐behavior longitudinally within serious games. Our multidimensional approach to assessing reward‐based game mechanics extends prior studies and suggests that higher‐tier rewards are more influential than lower‐tiered rewards to achieve sustainability marketing outcomes. We further demonstrate that reward‐based game mechanics outperform meaningful game mechanics at influencing desired outcomes, challenging existing gaming literature.